PERUBAHAN KOMBINASI WARNA BUSANA ADAT PENGANTIN TRADISIONAL WANITA LINTAU BUO SUMATERA BARAT - Rada Natalia Putri; Yuliarma Yuliarma (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
The city of Bukttinggi is one of the central areas of the famous embroidery craft in West Sumatra. One of the superior handicraft products from the city of Bukittinggi is embroidery which is well known to foreign countries. One of the functions of embroidery is to decorate clothes and develop creativity which is contained in various forms of patterns and images on cloth as decoration. In addition to the characteristics of the embroidery in the City of Bukittinggi, namely the motifs or models that were developed did not experience much change, in general, the motifs developed were patterned with the characteristics of embroidery from Bukittinggi. This research method is descriptive qualitative. Various types of data, including primary data and secondary data. craftsmen and embroidery business owners in the city of Bukittinggi who were the subjects of this research informant. Data collection techniques were through interviews, observation, and documentation. Data reduction, data presentation, and conclusion drawing are interactive model analysis techniques used in data analysis techniques. The results of this study can be seen that the types of suji embroidery products are: shawls and brackets